(untitled) (Practitioner Research, 2023)
In this article, we present the development of a module for Emotional Intelligence to foster organizational leadership in Nepal through the use of Collaborative Autoethnography (CA), a qualitative research method. The authors use their personal experiences related to the development of the module, its facilitation, and its impact when implemented in one of the organizations in Nepal to share their personal journey and the lessons learned. The reflections illustrate how participation in an EI module helped the organization gain insights into its leadership approach. The article also demonstrates how reflecting on the experiences helps both the facilitators and the participants draw tangible lessons associated with the content, to further improve their practice.